Studies on the action of Tamarind (Tamarindus indica) seed extract against some biological properties of King Copra (Ohiophagus Hannah) venom - Maung, Khin Maung; Oothumann , Paakeer; Al-Ani, Imad Matloub Dally (2013)
Annually it has been reported that there are 1.25 million deaths due to snake bite. With the aims of finding herbal remedies that could work synergistically with ant-snack venom, many studies were conducted. It has been shown that ethanolic extract of Tamarind (Tamarindus indica) seed (TSE) has inhibitory effects against lethal action of Vipera russelli and Doboia russelli siamensis. Thus the action of TSE on some biological properties of King Copra (Ohiophagus Hannah) venom (KCV) was studied. KCV was injected subcutaneously into skin of mice and after30 minutes and one hour. TSE was injected subcutaneously near the same site where the venom was injected. None of the mice died, however 4 out of 5 mice of the control group die. To test the effects of myonecrotic action, KCV was injected into the thigh muscles and after one hour, TSE was injected near the same site. Out of 4 mice of each group, 2 mice die before 24 hour. After 24 hour of venom injection, serum creatinine kinase enzyme activity of the surviving mice was measured. The enzyme activity of the TSE treated group was lower than that of the venom control group, but was not statistically significant. Histological study of the muscle was also conducted and found that TSE treated group showed less muscle necrosis than the control group. Thus TSE can neutralize some biological properties of the KCF.